The prosecution of bias crime in the Netherlands and the problem of net-widening: fundamental limits to criminal liability - Ringnalda, Allard (Crime, law and social change, 2012)
Crimes that are committed with bias motives are categorised as ‘hate’ or bias crimes and are punished more severely than nonbias crimes. However, bias crime laws are often applied to offences where there is no clear evidence of a bias motive. Based on the results of 318 case studies into bias crime prosecutions in the Netherlands, this paper demonstrates that the causes of net-widening should be sought in the action-oriented nature of criminal law reasoning. Decision makers rely on objective behavioural indicators to infer motives. However, these are rarely reliable. We argue that this process results in a transformation of bias crime laws. They are no longer used to punish harmful motives. Rather, they are used to combat behaviour that is considered socially harmful on account of its perceived intolerant, racist or xenophobic message. This forces us to reconsider the justification behind trying to punish motive.